INTEGRATION OF PANCASILA VALUES IN EFFORTS TO DEVELOP THE CHARACTER OF STUDENTS: THE CASE OF MI PSM PUPUS LEMBEYAN MAGETAN - Dian Nafi Firdhaus (Universitas Pendidikan Indonesia, 2022)
The purpose of this study 1) What is the Integration of Pancasila Values at MI PSM Pupus Lembeyan Magetan. 2) What is the Background of the Integration of Pancasila Values in MI PSM Pupus Lembeyan Magetan. 3) What are the Problems and Problems in the Integration of Pancasila Values at MI PSM Pupus Lembeyan Magetan. Purposive sampling of data sources by determining the head of the Madrasah, religious teachers, and several students in grades 4 and 5 with certain considerations. The research method used is qualitative with a case study approach, then the researcher analyzes the data through data collection by means of interviews, observation and documentation. Then the data is adjusted to the research focus, the last stage is drawing conclusions. The results of the study indicate the low level of understanding of students in understanding character values. The planting of Pancasila character values in Madrasas is expected to provide provisions for students to get along in their playing environment, in the PSM Madrasah environment the Pancasila characters are accustomed to social behavior and attitudes that are reflected from educators to students, in every learning process in Madrasas